Corporate Social Responsibility - Matten, Dirk (Journal of business ethics, 2004)
In the context of some criticism about social responsibility education in business schools, the paper reports findings from a survey of CSR education (teaching and research) in Europe. It analyses the extent of CSR education, the different ways in which it is defined and the levels at which it is taught. The paper provides an account of the efforts that are being made to ‘‘mainstream’’ CSR teaching and of the teaching methods deployed. It considers drivers of CSR courses, particularly the historical role of motivated individuals and the anticipation of future success being dependent on more institutional drivers. Finally it considers main developments in CSR research both by business school faculty and PhD students, tomorrow’s researchers and the resources devoted to CSR research. The conclusion includes questions that arise and further research directions.